Taking fishers’ knowledge and it's implications to fisheries policy seriously - Renck, Vitor; Ludwig, David; Bollettin, Paride [UNESP]; Reis-Filho, José Amorim; Poliseli, Luana; El-Hani, Charbel N. (Resilience Alliance, 2023)
Sustainable fishing is one of the most pressing challenges for mankind and requires insightful knowledge of the drivers that may foster or hinder predatory exploitation. It has been widely recognized that Indigenous and local knowledge can contribute to biodiversity conservation and sustainable use of resources, such as fisheries, worldwide. Nevertheless such knowledge continues to be marginalized and unacknowledged by a range of academic scientists and policy makers. In the present paper, we tackle this issue by discussing laws regarding closed fishing seasons, which are part of the Brazilian environmental policies for protecting marine fauna, from the perspective of artisanal fishers’ knowledge. In Brazil, these laws are typically based on governmental decisions (i.e., by administrative organizations and researchers acting as consultants) without taking fishers’ knowledge into account. Through semi-structured interviews with traditional experts of fishing villages situated along the northeast coast of Brazil, we aimed to investigate their knowledge of fish reproductive periods and analyze how it is related to the closed seasons at work in their region. We found an exact agreement between fishers’ knowledge and closed season regulations on the reproductive period of the mangrove crab (Ucides cordatus), but a conflict regarding the reproductive period of two snook species and four species of shrimps. We highlight the potential of fishers’ knowledge contributions to environmental regulations and we also explore three challenges of incorporating epistemic diversity in environmental policy. We conclude by advocating for a reflexive transdisciplinarity that highlights the potential of Indigenous and local knowledge while critically reflecting on the methodological and political challenges of transdisciplinary practices.
Keywords: artisanal fishers; closed fishing season; environmental policies; Indigenous and local knowledge; policy making; transdisciplinarity